Titanium dioxide nanoparticles affect osteoblast-derived exosome cargos and impair osteogenic differentiation of human mesenchymal stem cells - de Souza, Wanderson; Gemini-Piperni, S.; Grenho, Liliana; Rocha, Luís A. [UNESP]; Granjeiro, José M.; Melo, Sonia A.; Fernandes, Maria H.; Ribeiro, Ana R. (Royal Society of Chemistry (RSC), 2023)
Titanium (Ti) and its alloys are the most widely used metallic biomaterials in total joint replacement; however, increasing evidence supports the degradation of its surface due to corrosion and wear processes releasing debris (ions, and micro and nanoparticles) and contribute to particle-induced osteolysis and implant loosening. Cell-to-cell communication involving several cell types is one of the major biological processes occurring during bone healing and regeneration at the implant-bone interface. In addition to the internal response of cells to the uptake and intracellular localization of wear debris, a red flag is the ability of titanium dioxide nanoparticles (mimicking wear debris) to alter cellular communication with the tissue background, disturbing the balance between osseous tissue integrity and bone regenerative processes. This study aims to understand whether titanium dioxide nanoparticles (TiO2 NPs) alter osteoblast-derived exosome (Exo) biogenesis and whether exosomal protein cargos affect the communication of osteoblasts with human mesenchymal stem/stromal cells (HMSCs). Osteoblasts are derived from mesenchymal stem cells coexisting in the bone microenvironment during development and remodelling. We observed that TiO2 NPs stimulate immature osteoblast- and mature osteoblast-derived Exo secretion that present a distinct proteomic cargo. Functional tests confirmed that Exos derived from both osteoblasts decrease the osteogenic differentiation of HMSCs. These findings are clinically relevant since wear debris alter extracellular communication in the bone periprosthetic niche, contributing to particle-induced osteolysis and consequent prosthetic joint failure.